Sensitivity Improvement of an Optical Fiber Sensor Based on Surface Plasmon Resonance with Pure Higher-Order Modes - Chuanhao Yang; Bing Yan; Qi Wang; Jing Zhao; Hongxia Zhang; Hui Yu; Haojun Fan; Dagong Jia (Applied Sciences, 2023)
In this paper, we propose an approach to improve the sensitivity of an optical fiber surface plasmon resonance (SPR) sensor with a pure higher-order mode excited by a designed mode selective coupler (MSC). We calculate the proportion of the power of the higher-order mode in the cladding. Compared to the <semantics>LP01</semantics> mode, the power proportion of the <semantics>LP11</semantics> mode (<semantics>LP21</semantics> mode) in the cladding theoretically improves by 100% (150%). To generate a relatively pure <semantics>LP11</semantics> mode or <semantics>LP21</semantics> mode, a mode selective coupler (MSC, 430–580 nm) is designed. The coupling efficiency of the <semantics>LP01–LP11</semantics> mode coupler is over 80%, and that of the <semantics>LP01–LP21</semantics> mode coupler is over 50%. The simulation results show that the sensitivity of the <semantics>LP11 </semantics> mode and the <semantics>LP21</semantics> mode increases by approximately 330% and 360%, respectively, using the intensity modulation (n = 1.33–1.38, 430–580 nm); the resolution of the refractive indices of our sensor, using the <semantics>LP11</semantics> mode (<semantics>LP21</semantics> mode), is <semantics>2.6×10−4</semantics> RIU (<semantics>2.4×10−4</semantics> RIU). The higher sensitivity and resolution of our presented fiber SPR sensor containing a visible MSC make it a promising candidate for the measurement of refractive indices.